CHARACTERIZATION OF GENETIC RESOURCES AND IDENTIFICATION OF SUITABLE BRINJAL (SOLANUM MELONGENA L.) GENOTYPES IN MALWA PLATEAU REGION OF MADHYA PRADESH - NANCY JASWANI, DEEKSHA TEMBHRE, SMITA AGRAWAL, S. KADWEY, SUNIL PRAJAPATI ASHWINI DADIGA (The Bioscan, 2015)
A field experiment was conducted to assessment of yield potential brinjal genotypes for commercial production in western part of Madhya Pradesh. Among the diverse 15 genotypes, Pusa Purple Cluster was recorded significantly higher potential in most of traits viz., highest plant height at 90 DAT(92.5cm), number of branches plant-1at 90 DAT (19.9cm), leaves plant-1at 90 DAT(115.3), leaf length at 90 DAT(13.4cm), fresh weight plant-1(997.8g),dry weight plant-1(239.9 g), LAI(3.70), highest (6.65mg/cm/day) NAR was found in Shilpa F1 hybrid, (6.59mg/cm2/ day), (0.25g/m2/day) CGR was found in genotype Pusa Purple Cluster. Pusa Purple Cluster was observed significantly superior which recorded number of fruits plant-1(24.6)followed by Green Express-666 (19.5),Genotype Kanahiya was maximum in fruit weight(166.3 g) followed by Vijay SGS-548(153.4 g), Genotype Pusa Purple Cluster was superior and gave maximum (36.2 t ha-1) (1.856 kg plant-1) Green Express-666 (F1) (34.5t ha-1), (1.75 kg plant-1) fruit yield ha-1 and yield plant-1 respectively, maximum fruit yield of (36.25 t ha-1) was obtained in brinjal variety Pusa Purple Cluster with net return of Rs. 319584 ha-1 and cost benefit ratio 1: 8.45 followed by Green Express-666 (F1).